Формування критерію безпечного управління поїзною роботою на залізничній станції - Лаврухін, О. В. (НТУ "ХПІ", 2014)
Роботу присвячено формуванню критерію безпечного управління поїзною роботою на залізничній станції, який надає можливість якісно оцінити рівень безпеки виконання експлуатаційної роботи оперативним персоналом при управлінні поїзними пересуваннями без застосування автоматизованих робочих місць на протязі робочої зміни. В процесі виконання наукової роботи було розраховано критерій безпечної експлуатації б K, сортувальної позакласної станції Харківської дирекції залізничних перевезень Південної залізниці Основа, за результатами якого станцію було віднесено до 4 рівня безпеки.

The paper is devoted to the formation of criteria for safe train operation control at the railway station, which allows you to qualitatively assess the performance of operational safety of operating personnel in the management of train movements without the use of computer workstations throughout the work shift. In carrying out scientific work was calculated criterion safe operation, sorting out-station of Kharkov railway department of the Southern Railway Base, which resulted in the station was classified as level 4 security. These zanchennya indicate the need to implement measures to improve the security of a linear object, based technology can be used as automated control.
Criterion of safe performance management train at a railway station
Keywords: безпека; функція приналежності; негабаритний вантаж; спеціалізована колія; security; secure management criteria; membership function; oversized cargo